IMPLEMENTASI KEBIJAKAN KAMPANYE MELALUI MEDIA SOSIAL PADA PEMILIHAN UMUM KEPALA DAERAH KABUPATEN JAYAPURA TAHUN 2017 - Sunggul Sinurat; Akbar Silo (JURNAL KEBIJAKAN PUBLIK, 2023)
The use of social media in political campaigning today has become a new trend in maximizing the dissemination of information more comprehensively. This study aims to analyze and describe the implementation of campaign policies through social media in the 2017 Jayapura District Election and analyze the supporting and inhibiting factors. This study used a qualitative descriptive approach which was carried out at the Jayapura Regency KPU, and the determination of informants was carried out by snowball. Data collection techniques used are observation and interviews. Data analysis includes the stages of data reduction, data presentation, and conclusion. The results of the study show that the implementation of campaign policies through Social Media for the 2017 Jayapura District Election has been running but not yet effective. In terms of communication and information dissemination aspects, it has been carried out as it should, by providing outreach to the campaign team. In terms of resources, supporting resources and adequate human resources have been available to convey information and physical facilities as a meeting place between the KPU and the campaign team. The disposition of policy implementers has complied with policy rules and orders. Then, the Bureaucratic Structure, KPU Jayapura Regency does not yet have detailed guidelines regarding campaigns through social media in the 2017 Pilkada. The supporting factors are the availability of a help desk Consultation Team and the existence of an election smart house. Then the inhibiting factors are the lack of public understanding of the use of social media, limited internet access, and public apathy.